2021
DOI: 10.1016/j.envint.2021.106524
|View full text |Cite
|
Sign up to set email alerts
|

Association between urinary per- and poly-fluoroalkyl substances and COVID-19 susceptibility

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…Connectome analysis could include more diverse age groups, especially adolescents. Additionally, the integration of results from different connectomes, including connectomes based on proteomics, metabolomics, transcriptomics and exposomics, may prove more informative than analyses based on a single connectome [ 149 , 150 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Connectome analysis could include more diverse age groups, especially adolescents. Additionally, the integration of results from different connectomes, including connectomes based on proteomics, metabolomics, transcriptomics and exposomics, may prove more informative than analyses based on a single connectome [ 149 , 150 ].…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…These concentrations were 135, 35, and 5 times higher than those measured in the reference population from Karlshamn. To put these exposure levels into context, Ji et al [8] performed their study in a population with median serum…”
Section: Discussionmentioning
confidence: 99%
“…From a public health perspective, it is highly relevant to clarify whether PFAS also increases the susceptibility to SARS-CoV-2 because such knowledge would aid in identifying individuals at higher risk of infection. A recent case-control study of 160 participants from Shanxi and Shandong, Chinese provinces with both high PFAS exposure and high incidence of COVID-19, showed increased odds ratios of mild infection with increasing urine concentrations of PFOS, PFOA, and the sum of 12 PFAS [8]. Taken together, these studies provide some evidence that exposure to PFAS may indeed play a role in the clinical course of COVID-19, but further studies are needed to verify the findings.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, a computational systems biology approach was used to study the relationship between EDCs and COVID-19 severity and identified the T-helper cell 17 (Th17) and the advanced glycation end products/receptor for advanced glycation end products (AGE/RAGE) pathways as principal targets through which EDCs could contribute to COVID-19 severity [20]. A non-mechanistic study that analyzed the urine and serum concentrations of Per-and poly-fluoroalkyl substances (PFASs) found a positive association between urinary levels of perfluorooctanesulfonic acid (PFOS) (odds ratio: 2.29 (95% CI: 1.52-3.22)), perfluorooctanoic acid (PFOA) (2.91, (1.95-4.83)), and total PFASs (Σ (12) PFASs) (3.31, (2.05-4.65)) with the risk of COVID-19 infection [137]. These preliminary studies provide insight into how EDCs can influence the clinical outcome of COVID-19 disease.…”
Section: Current Knowledge On Edcs and Covid-19 Risksmentioning
confidence: 99%